Histone deacetylase activity of Rpd3 is important for transcriptional repression in vivo - Kadosh, David (Cold Spring Harbor Laboratory Press, 1998)
Eukaryotic organisms from yeast to human contain a multiprotein complex that includes Rpd3 histone deacetylase and Sin3 corepressor. The Sin3–Rpd3 complex, when recruited to promoters by specific DNA-binding proteins, can direct transcriptional repression of specific classes of target genes. It has been proposed that the histone deacetylase activity of Rpd3 is important for repression, but direct evidence is lacking. Here, we describe four Rpd3 derivatives with mutations in evolutionarily invariant histidine residues in a putative deacetylation motif. These Rpd3 mutants lack detectable histone deacetylase activity in vitro, but interact normally with Sin3 in vivo. In yeast cells, these catalytically inactive mutants are defective for transcriptional repression. They retain some residual Rpd3 function in vivo, however, suggesting that repression by the Sin3–Rpd3 complex may not be attributable exclusively to its intrinsic histone deacetylase activity. Finally, we show that a human Rpd3 homolog can interact with yeast Sin3 and repress transcription when artificially recruited to a promoter. These results suggest that the histone deacetylase activity of Rpd3 is important, but perhaps not absolutely required, for transcriptional repression in vivo.